Neural plasticity in early potters: Shape analysis and TMS-EEG co-registration trace the rise of a new motor skill. - Vanessa Forte; Luisa Sartori; Antonino Visalli; Mustafa Yildirim; Gaspare Galati; Massimo Vidale; Emanuela Faresin; Antonino Vallesi (PLoS ONE)
In this study, we explored the biocultural mechanisms underlying ancient craft behaviours. Archaeological methods were integrated with neuroscience techniques to explore the impact on neuroplasticity resulting from the introduction of early pottery techniques. The advent of ceramic marked a profound change in the economy and socio-cultural dynamics of past societies. It may have also played a central role in developing new craft skills that influenced the neural plasticity of the potters. Coiling, one of the most widespread neolithic techniques, requires precise hand movements and the ability to regulate finger pressure to shape the clay without deformation. In a pilot study involving intensive training in neolithic pottery, we used TMS-EEG co-registration to monitor a group of participants and we examined the shape of the artefacts they made before and after training. Our findings suggest changes in the functional properties of the primary motor cortex (M1) responsible for the control and execution of actions. We also observed an improvement in symmetry and consistency of the artefacts and a significant reduction in errors. This multidisciplinary approach sheds light on the mechanisms of material culture's variation in the archaeological field and provides promising insights into the co-evolution of technology and human skill.